2017
DOI: 10.1192/bjp.bp.116.185421
|View full text |Cite
|
Sign up to set email alerts
|

Are some of the stigmas of addictions culturally sanctioned?

Abstract: We provide three examples of how addiction stigma is sanctioned: (a) discrimination against people with addictions is often legal; (b) public health communications frequently use stigma to promote prevention; (c) some programmes, such as '12 steps' promote self-stigma. The implications of sanctioned stigma for stigma-change programmes are then discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 7 publications
(5 reference statements)
0
23
0
Order By: Relevance
“…Drug-and alcohol-related death are likely to have different consequences for the bereaved (Valentine and Bauld 2018, p. 2, 7). Using drugs is an illegal activity and the addiction stigma is likely to be worsened by criminalization, since drug use is conflated with felonious conduct (Corrigan et al 2017). Furthermore, people who die from an overdose are more likely to be male and young and to suffer a death that occurs early in the course of addiction (Templeton et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug-and alcohol-related death are likely to have different consequences for the bereaved (Valentine and Bauld 2018, p. 2, 7). Using drugs is an illegal activity and the addiction stigma is likely to be worsened by criminalization, since drug use is conflated with felonious conduct (Corrigan et al 2017). Furthermore, people who die from an overdose are more likely to be male and young and to suffer a death that occurs early in the course of addiction (Templeton et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Goffman (1963) wrote about 'spill over', where an individual's 'stains' spill over to the next of kin in such a way that the social discredit affects them to the same degree. In this way, family members themselves become stigmatized through association with a relative who uses drugs (Corrigan et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in Norway, individuals scoring higher in authoritarian beliefs were found to make more judgments of personal responsibility, which negatively affected their willingness to support public funding to help people with addiction [13]. Corrigan, Schomerus, and Smelson [14] note that discrimination against PWUDs is accepted by society. Indeed, the use of many drugs, such as opioids, is illegal and treated criminally.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In response to our editorial in the BJPsych , 1 Ginn & Clark note that medical professionals add to the stigma of substance use disorders. Sadly, their insights parallel the larger research on the stigma of mental illness and psychiatry: namely, psychiatric service providers tend to be among the most stigmatising of professions.…”
mentioning
confidence: 99%